2022
DOI: 10.3389/fneph.2022.926635
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 neutralizing antibody response after three doses of mRNA1273 vaccine and COVID-19 in hemodialysis patients

Abstract: BackgroundIn hemodialysis patients, a third vaccination is frequently administered to augment protection against coronavirus disease 2019 (COVID-19). However, the newly emerged B.1.1.159 (Omicron) variant may evade vaccinal protection more easily than previous strains. It is of clinical interest to better understand the neutralizing activity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants after booster vaccine or COVID-19 infection in these mostly immunocompromised patients.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Seropositivity and MAB level in both groups increased rapidly 2 weeks after the third dose (TP4) and showed further increase over the following one year with 100% seroconversion and comparably high MAB levels in both groups. Although there are fewer data available regarding the immune response to 3 dose-mixed vaccination in HD patients, several countries have studied the immune response to 3 doses of mRNA vaccines (BNT162b2 and/ or mRNA-1237) where seroconversion rates ranged between 95–98.5% [ 16 , 29 – 31 , 56 , 57 , 61 ] with increased antibody titres (SARS CoV-2 anti-spike IgG) that ranged between 9910 AU/ml and 26037AU/ml within 1–3 months of receiving the third booster dose. HD patients were shown to maintain seropositivity at 98.3% four months after the third dose, though MAB levels reduced [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seropositivity and MAB level in both groups increased rapidly 2 weeks after the third dose (TP4) and showed further increase over the following one year with 100% seroconversion and comparably high MAB levels in both groups. Although there are fewer data available regarding the immune response to 3 dose-mixed vaccination in HD patients, several countries have studied the immune response to 3 doses of mRNA vaccines (BNT162b2 and/ or mRNA-1237) where seroconversion rates ranged between 95–98.5% [ 16 , 29 – 31 , 56 , 57 , 61 ] with increased antibody titres (SARS CoV-2 anti-spike IgG) that ranged between 9910 AU/ml and 26037AU/ml within 1–3 months of receiving the third booster dose. HD patients were shown to maintain seropositivity at 98.3% four months after the third dose, though MAB levels reduced [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…HD patients were shown to maintain seropositivity at 98.3% four months after the third dose, though MAB levels reduced [ 16 ]. Importantly, low to moderate levels of Omicron neutralization were seen in patients only after either 3rd dose vaccination or post COVID-19 infection [ 50 , 57 ]. Further, while patients who had COVID-19 (after 2 previous doses) developed nAB levels similar to those who had 3rd dose vaccination (2200 -2500 IU/ml), those who had infection, had a 3.2 fold higher level of Omicron nAB compared to post vaccination individuals [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Wang et al compared the neutralizing antibody response in dialysis patients to both WT and omicron variants and found that the vaccine response against Omicron was significantly less compared with that against WT. 31 Additionally, the half‐life of the omicron antibody response was shorter than that of the WT. These findings likely account for our rapid increase in antibody level in patients who were infected postbooster and the subsequent rapid decline.…”
Section: Discussionmentioning
confidence: 99%
“…Although COVID-19 vaccine boosters are highly effective in enhancing immunity against SARS-CoV-2 variants in HD patients, their optimal doses and durability are still uncertain in this population [ 52 ]. A previous study in Israel demonstrated that the third dose of the BNT162b2 vaccine induced a more durable humoral response than the second dose in healthcare workers, and the reliable neutralizing capacity for the Omicron variant could persist for at least four months [ 53 ].…”
Section: Discussionmentioning
confidence: 99%